249 PERSEPSI ALUMNI TERHADAP PELATIHAN MANAJEMEN KESEJAHTERAAN SOSIAL DI BBPPKS BANDUNG - Rohmat, Dewi Nur; Ardiwinata, Jajat S.; kamarubaini, Nita (PEDAGOGIA, 2015)
This research background for the many social problems that occur in children, the Institute of Social Welfare of the Child (LKSA) which has the duties and functions as an organizer of parenting, it is expected to increase the competence of managers LKSA (Institute of Social Welfare of the Child) in order to overcome the problems that occur in family. This research includes: 1) To obtain a picture of the implementation of the Management Training for Social Welfare based aspects: training materials, learning methods, trainers, trainees, training facilities and training evaluation, 2) To know the perception of the alumni of the Management Training for Social Welfare in BBPPKS Bandung based on gender, age, educational background, occupation and province of origin of the work. The method used is descriptive method with quantitative approach. Data collection techniques used are questionnaire and documentation. The population in this study is an alumni social welfare management trainee in BBPPKS Bandung totaling 30 people. The results showed perceptions of alumni of the Management Training for Social Welfare in BBPPKS Bandung based aspects of training materials, learning methods, trainers, trainees, training facilities, and the evaluation of training in the category of "high" which indicates that the ManagementTraining Social Welfare who has been held by BBPPKS Bandung is good enough because there is at "high". Based on the results obtained percentage score, sex male, between 19-26 years of age, educational background Diploma, board positions and alumni who came from West Java Province has the result scores the highest percentage.Keywords: Welfare, Social, Evaluation, Training.